Multi-Ethnic and Multi-Religious Involvement of Indonesian-Chinese Muslims Society in Habituating the Indonesian Nation Character - Berliana, Religia Fatihasari; Rusnaini, Rusnaini; Triyanto, Triyanto (Budapest International Research and Critics University, 2021)
Together with the meaning of unity in diversity, Indonesia had been known as one of the country in the world who had a wonderful spirit on keeping unite in the diversity. Known as having Bhinneka Tunggal Ika, Indonesian people lived harmoniously within multicultural, multireligion, and multiethnic society which had been shaped since centuries ago. Living along different ethnical background or religion background did not make Indonesian people ignored the existence of minorities. Indonesian people nowadays, did not differenciate the majorities or the minorities. Talking about nation character, it was an important duty for all Indonesian people. The purposes of this research were to find out the implementation of habituating the nation character of Chinese-Muslims in Muhammad Cheng Hoo Hajj Foundation Indonesia. This research used qualitative methods with descriptive research as the type of research. The data consisted of Informant, Observation, and Document. The results of this research were: Muhammad Cheng Hoo Hajj Foundation Indonesia had some activities that are related to nation character building. This foundation had many activities with cross-religion, cross-cultural, and cross-ethnical organization.